Selected risk factors for atherosclerosis in children and their parents with positive family history of premature cardiovascular diseases: a prospective study - Elzbieta Pac-Kozuchowska; Paulina Krawiec; Ewelina Grywalska (BMC, 2018)
Abstract Background The aim of the study was to evaluate serum parameters of lipid metabolism, homocysteine, soluble adhesion molecules and common carotid artery wall thickness in children from families with early symptoms of atherosclerosis. Methods The first stage included 137 pairs of mothers and newborns, and the second 18 children from the same group (age 18-30 months) and their parents (age 21-46 years) with a history of premature coronary artery disease (CAD), as well as 12 age- and sex-matched controls. Results During the first stage, inverse correlations were found between birthweight, cord blood concentrations of triglycerides (TG), VLDL cholesterol and apolipoprotein B (Apo B). Serum concentrations of total cholesterol (TC), apolipoprotein A1 (Apo A1), LDL and HDL cholesterol and were significantly higher in female than in male newborns. During the second stage, children from families with a history for premature CAD were shown to present with significantly higher serum concentrations of TG, VLDL cholesterol and lipoprotein A (Lp(a)) than the controls. Furthermore, their TC correlated positively with vascular cell adhesion molecule-1 (Rs=0.717, p<0.05) and intracellular adhesion molecule-1 (sICAM-1) levels (Rs=0.833, p<0.05). Moreover, positive correlations were found between maternal carotid intima media thickness (IMT) and TC (Rs=0.831, p<0.01), as well as between paternal IMT and Apo B (Rs=0.692, p<0.05), TG and sICAM-1 (Rs=0.912, p<0.01), TG and sE-selectin (Rs=0.678, p<0.05). Conclusions Serum Lp(a) may serve as a maker of cardiovascular risk in children and adolescents.